Rituximab in early systemic sclerosis. Issue 2 (28th July 2017) - Boonstra, Maaike; Meijs, Jessica; Dorjée, Annemarie L; Marsan, Nina Ajmone; Schouffoer, Anne; Ninaber, Maarten K; Quint, Koen D; Bonte-Mineur, Femke; Huizinga, Tom W J; Scherer, Hans U; de Vries-Bouwstra, Jeska K
Abstract : Objectives: (1) Hypothesis testing of the potency of rituximab (RTX) in preventing fibrotic complications and (2) assessing acceptability and feasibility of RTX in early systemic sclerosis (SSc). Methods: A small, 24-month, randomised, double-blind, placebo-controlled, single-centre trial in patients with SSc diagnosed <2 years was conducted. Patients received RTX or placebo infusions at t=0, t=15 days and t=6 months. Patients were clinically evaluated every 3 months, with lung function tests and high-resolution CT every other visit. Skin biopsies were taken at baseline and month 3. Immunophenotyping of peripheral blood mononuclear cells was performed at every visit, except at months 9 and 18. Adverse events, course of skin and pulmonary involvement and B cell populations in skin and peripheral blood were evaluated. Results: In total 16, patients (rituximab n=8, placebo n=8) were included. Twelve patients had diffuse cutaneous SSc. Eighty-eight adverse events (RTX n=53, placebo n=35, p=0.22) and 11 serious adverse events (RTX n=7, placebo n=4, p=0.36) occurred. No unexpected RTX-related events were observed. Mean skin score over time did not differ between the groups. Over time, forced vital capacity and extent of lung involvement slightly improved with RTX, but this difference was insignificant. In peripheral blood B cells depletion was demonstrated. Conclusions: No unexpected safety issues were observed with RTX in early SSc. Although this small trial could not confirm or reject potential efficacy of RTX in these patients, future placebo-controlled trials are warranted, specifically in the subgroup of patients with pulmonary involvement. Trial registration number: EudraCT 2008-07180-16; Results.